Characterization and genetic diversity of grapevine Pinot gris virus in Serbian vineyards - Sanja ŽIVKOVIĆ; Bojana VASILIJEVIĆ; Tanja VASIĆ; Debasis MITRA; Darko JEVREMOVIĆ (Phytopathologia Mediterranea)
Sixty-five samples of grapevine from commercial vineyards in the Rasina district of Serbia were tested for the presence of grapevine Pinot gris virus (GPGV), using the reverse transcription-polymerase chain reaction. Fourteen samples of the grapevine varieties ‘Red Globe’, ‘Victoria’ and ‘Preobraženje’ were infected with GPGV. All the infected plants showed symptoms of leaf chlorotic mottling, puckering, and deformation, stunting, and reduced yields. The coding regions of the movement and coat protein (MP/CP) and a region of the RNA-dependent RNA polymerase (RdRP) domains of eight virus isolates were sequenced. Phylogenetic analyses of these genomic regions showed high nucleotide similarity among the Serbian GPGV isolates. This study is the first to describe genetic diversity of GPGV isolates in Serbia.